Platelet turnover and function in end-stage renal disease - Filipov, Predrag T; Dušan, Božić; Romana, Mijović; Gorana, Mitić (Vojnosanitetski pregled, 2020)
Background/Aim. End-stage renal disease (ESRD) is characterized by significant impairment of platelet functions which may cause bleeding or thrombotic complications. The iam of this study was the aim of this study was the assessement of platelet turnover and function and their correlation with inflammatory and procoagulant markers in ESRD patients as well as platelet indicies comparison between ESRD diabetic and ESRD non-diabetic patients. Methods. The prospective, observational clinical study included 63 ESRD patients and 30 age and sex matched healthy volunteers. Following laboratory parameters of platelet turnover and function (platelet count, reticulated platelets, platelet indices, whole blood impedance platelet aggregation), inflammatory and procoagulant markers (number of neutrophils, neutrophil to lymphocyte ratio, C-reactive protein, plasma fibrinogen, D dimer, von Willebrand factor) were obtained. Results. Platelet turnover (% of reticulated platelets) was significantly higher (3.8 ± 2.3 vs. 2.3 ± 1.3; p < 0.01) and platelet aggregation tests induced by thrombin receptor activiting peptide (TRAP) (p < 0.01), adenosine diphospate (ADP) (p < 0.05), arachidonic acid (ASPI) (p < 0.05) and collagen (p < 0.05) were markedly increased in the ESRD patients compared to the control group. The comparison of chronic inflammation and procoagulant markers revealed higher values in all patients comparing to the group of healthy subjects (p < 0.01 regarding all parameters). There was no difference between the ESRD diabetic and ESRD non-diabetic patients. Conclusion. Results point out increased platelet turnover in ESRD as a consequence of platelet activation and consumption induced by clotting system hyperactivity and chronic inflammation. None of the examined parameters do not predict bleeding occurrence.
Keywords: kidney failure, chronic; diabetes mellitus; platelet funcion tests